ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUTRI ARAK DI DESA TRI EKA BUANA - Dyah Dwiantari I Gusti Agung; Sudiana I Ketut (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2019)
This study aims to analyze the influence of capital, raw materials, labor, work experience simultaneously and partially to the production of arak industry in Tri Eka Buana Village. And the dominant variables affect the production of the arak industry. The result of research stated that capital, raw material, labor and work experience simultaneously have positive and significant effect to production in arak industry in Tri Eka Buana Village Sidemen Sub-district of Karangasem Regency. In partial capital, raw materials, labor has a positive and significant effect on the production of the arak industry. While the work experience does not have a positive and partially significant effect on the production of the arak industry with the value of work experience (0,454) <ttabel (1,671) also supported by the coefficient ?4 = 0,014, It means that there is no direct relationship between work experience with production in the arak industry . The dominant variable affecting the production of the arak industry in Tri Eka Buana Village Sidemen Subdistrict Karangasem Regency is the raw material. The makers of arak are advised to improve their skills, training and innovate in processing or when looking for raw materials that will improve and produce better products and quality.